Applying religion and film to Islam - L. Blizek, William; Yorulmaz, Bilal (Global Journals Inc. (USA), 2015)
“Religion and film studies” is an academic field that includes a wide variety of activities and interests. In the early years, religion and film studies focused upon Christianity and Judaism in the movies, including a number of famous Bible stories. In the past several years, however, religion and film studies has widened considerably and now includes movies about Hinduism, Buddhism, Islam and other religions. As more movies about Islam become widely available, as more Hollywood films deal with issues related to Islam, and as more Muslim scholars turn their attention to film, we can expect an increase in Islam and film studies. The purpose of this paper is to draw an early picture of what religion and film studies will look like in a Muslim context. The use of religion to interpret film will become more popular as filmmakers create more movies with Islamic subtexts. The use of film to critique religion will become more popular as a topic when more movies are made that critique Islam—its various branches and practices. And there will be an ongoing debate about when something is an attack on Islam and when something is a legitimate criticism. There also will be films that focus upon various themes from Islam. These themes will be different from the themes of other religions, but finding such themes in movies will become a popular activity. Some of those themes might include pilgrimage, prayer, fasting, or Ramadan. Religion and film studies is beginning to take notice of Islam and this should make for a very interesting addition to the previous discussions of religion and film.
Keywords: religion and film; islam; religious education